Experimental Study on Surface Quality of Hole and Biological Damage in Bone in Drilling - Alam, Khurshid; Iqbal , Muhammad; Al-Sumri, B.; Al-Kindi, Mohamed; Hewavidana, Yasasween; Silberschmidt, Vadim (CMBES Proceedings, 2023)
Drilling of bone with a hard metallic drill is a common surgical procedure used in various contexts in orthopedics, neurosur-gery, and dentistry. The performance of the process is based on the minimal invasion to the delicate bone tissue. Surface quality of the drill bit, the drilled hole and biological damage (death of bone cells) are the inevitable outcomes associated with the drilling process. Repeated use of surgical drills and other processes such as irrigation with saline solution and sterilization process causes wear of the cutting edges of the drill which can seriously affect its performance during operation. The aim of this study was to move a step forward towards minimally invasive surgical procedures in bones by investigat-ing the effect of wear of surgical drill bits on postoperative outcomes. The surface quality of the drill was found to influ-ence the surface of the drilled holes as well as the extent of biological damage around the drilling region. Worn drill pro-duced poor surface quality of the hole and caused more cells death near the drilling region compared to a sharp drill.